Sustained high HIV incidence among men who have sex with men in Jiangsu province, China: based on the limiting-antigen avidity EIA method and six consecutive surveys, 2016–2021 - Zhou, Ying; Chen, Yuheng; Lu, Jing; Zhang, Zhi; Sun, Qi; Liu, Xiaoyan; Xu, Xiaoqin; Ya, Xuerong; Hu, Haiyang (Frontiers in Public Health, 2023)
Background: Epidemic of HIV infection among men who have sex with men (MSM) is one of major public health concerns in some parts of China, but data on trends in HIV incidence are limited. This study aimed to examine the trends in HIV incidence and factors associated with recent HIV infection among MSM in Jiangsu province, China, based on limiting-antigen avidity enzyme immunoassay (LAg-Avidity-EIA) method.Methods: Six consecutive surveys were implemented among MSM throughout Jiangsu province from 2016 to 2021. Participants were recruited in three ways. Sociodemographic and behavioral information were collected through face-to-face interviews. Venous blood samples were taken to test for HIV and syphilis. HIV incidence was estimated by the LAg-Avidity-EIA method. Chi-square trend tests were used to observe trends over the years. Multivariate regression analyses were used to identify factors associated with recent HIV infection.Results: A total of 15401 participants were enrolled into the study. The prevalence of HIV infection ranged from 8.0% to 9.8%, with no consistent rise or fall over the years (P=0.189). HIV incidence ranged from 5.0% to 9.0%, and no uptrend or downtrend was shown, as well (P=0.418). MSM who lived locally for more than two years (aOR=1.366, P=0.019), were lack of comprehensive HIV knowledge (aOR=1.643, P=0.031), engaged in unprotected anal intercourse (UAI) in the past 6 months (aOR=7.373, P<0.001), were tested for HIV within 12 months (aOR=1.292, P=0.035), and tested positive for syphilis (aOR=2.840, P<0.001) were likely to be recently infected with HIV.Conclusions: HIV incidence among MSM has remained at a high level in Jiangsu province. In China, health education, condom use and HIV/syphilis testing should continue to be top priorities for HIV prevention among MSM to reduce HIV transmission.